2018
DOI: 10.1590/1808-165700x142015
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of trahira fish (Hoplias malabaricus) from Baixada Maranhense, municipality of São Bento, MA

Abstract: Fish are considered rich sources of nutrients. Health care throughout its production chain aims to ensure quality, minimizing the risks of transmission of foodborne diseases. In order to evaluate the microbiological quality of trahira fish (H. malabaricus), 40 samples were analysed for Most Probable Number (MPN) of coliforms at 45ºC, counts of aerobic mesophilic bacteria and Staphylococcus spp., identification of E. coli, Salmonella spp. and Aeromonas spp.. Analyses were conducted according to official methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(12 reference statements)
0
2
0
2
Order By: Relevance
“…Additionally, it is the second most common Salmonella serotype in Europe [18]. An epidemiological study of Salmonella typhimurium in Brazil, covering clinical samples and foods (poultry, chicken, pork and beef), was conducted in the regions of São Paulo, Santa Catarina, Paraná, Mato Grosso do Sul, Rio Grande do Sul, Goiás and Bahia [15,[19][20][21]. However, studies on fish are reported only in the states of Mato Grosso and Maranhão [15,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is the second most common Salmonella serotype in Europe [18]. An epidemiological study of Salmonella typhimurium in Brazil, covering clinical samples and foods (poultry, chicken, pork and beef), was conducted in the regions of São Paulo, Santa Catarina, Paraná, Mato Grosso do Sul, Rio Grande do Sul, Goiás and Bahia [15,[19][20][21]. However, studies on fish are reported only in the states of Mato Grosso and Maranhão [15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…An epidemiological study of Salmonella typhimurium in Brazil, covering clinical samples and foods (poultry, chicken, pork and beef), was conducted in the regions of São Paulo, Santa Catarina, Paraná, Mato Grosso do Sul, Rio Grande do Sul, Goiás and Bahia [15,[19][20][21]. However, studies on fish are reported only in the states of Mato Grosso and Maranhão [15,20,21]. In the study by [15], the Typhimurium serotype was detected in samples collected at a fish slaughterhouse during the transportation, washing with chlorinated water, evisceration, skinning and filleting stages.…”
Section: Introductionmentioning
confidence: 99%
“…É uma espécie neotropical pertencente à família Erythrinidae, sendo frequentemente utilizada para consumo humano, apresentando características produtivas desejáveis como adaptabilidade, alta taxa de proliferação e crescimento (LOZANO et al, 2014). Além disso, a traíra apresenta bom rendimento de carcaça e alta qualidade de carne, características que poderiam classificá-la como uma espécie alvo para a criação em cativeiro (GUIMARÃES et al, 2017;REIS et al, 2017).…”
Section: Introductionunclassified
“…).Destes microrganismos mencionados, no estado do Maranhão, daSilva Lopes et al (2012) relataram a presença de Aeromonas hydrophila em 45,24% das amostras de pescada amarela, Cynoscion acoupa desembarcadas em São Luís Ferreira et al (2014). relataram A. hydrophila em 15% das amostras de peixe serra, Scomberomerus brasiliensis, desembarcados no município de Raposa Guimarães et al (2017). também relataram a ocorrência das espécies A. cavie e A. hydrophila em 90% dos peixes analisados, além de Salmonella spp.…”
unclassified